Evaluation of Thyroid Ultrasound Report Quality and Assessing Effect of Adherence to Risk Stratification Criteria on Referral for Thyroid Nodule Biopsy. Issue 2 (May 2021) - Thejeel, Bashiar; Rahimi, Behruz; Seidler, Michael; Al-Agha, Rany; Fung, Christopher
Purpose: This study aims to evaluate the quality of diagnostic thyroid ultrasound reports and determine the impact of consistent adherence to 2015 American Thyroid Association (ATA) and 2017 American College of Radiology (ACR) Thyroid Imaging Reporting and Data System (TI-RADS) on reducing unnecessary referrals for thyroid nodule biopsy. Materials and Methods: Reports from 291 referrals for thyroid nodule biopsy were included for retrospective report evaluation (males: 42; mean age: 56) according to 2015 ATA and ACR TI-RADS lexicon. Cytology results were collected for each patient. Two radiologists blinded to cytology results independently, retrospectively reviewed imaging of the referrals, and rescored them according to 2015 ATA and 2017 ACR TI-RADS risk stratification systems. Statistical analysis was completed using chi-square analysis and calculation of κ statistic for interobserver variability. Results: No report completely addressed all features associated with malignancy. Over half of the reports did not include descriptors on echogenicity, shape, margin, or echogenic foci. In all, 9.3% of biopsies showed malignant histology. Rescoring of referrals demonstrated decrease in biopsy referrals by 55% as per 2017 ACR TI-RADS and 14% as per 2015 ATA ( P < .0001). There was no impact on detection of malignancy with adherence to ATA or ACR criteria and less interobserver variability with application of 2017 ACR TI-RADS compared to 2015 ATA. Conclusion: Thyroid ultrasound report quality was found variable with respect to nodule description. Reports recommended biopsy based on nodule size with no detailed description of other imaging features. Adherence to risk stratification system would have resulted in significant reduction in the number of unnecessary biopsy referrals.